Truncation of mutant huntingtin in knock-in mice demonstrates exon1 huntingtin is a key pathogenic form - Huiming Yang (Nature Portfolio, 2020)
The mechanisms by which mutant Huntington protein Htt leads to selective neurodegeneration are not fully understood. Here, using gene editing in HD140Q knock-in mice, the authors show that exon1 Htt is a critical pathological form of the protein.